Advances in Patterning Materials and Processes XXXII 2015
DOI: 10.1117/12.2086091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sequential infiltration synthesis on pattern fidelity of DSA lines

Abstract: Numerous block copolymer (BCP) systems can be used in directed self-assembly (DSA) processes to form patterns useful in lithography, especially lines and spaces with lamellar phase systems and vias/pillars with cylindrical phase systems. However, most of these BCP systems with attractive pattern formation capabilities have limited plasma etch contrast between the polymer domains. One potential solution to greatly enhance this etch contrast is a recently developed technique called sequential infiltration synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Moreover, the self-limiting nature of SIS leads to final features in which changes in volume are minimal and can be controlled by varying the number of SIS cycles or other SIS parameters such as adsorption/purge time or temperature . With regard to the effect of infiltration on pattern quality, there is evidence of improved line edge roughness (LER), especially for low- and midfrequency roughness regimes, whereas surface roughness, another sensitive parameter, showed a modest increase after infiltration . Roughness analysis in ref was performed on the top surface of PMMA/SIS sub-100-nm lithographic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the self-limiting nature of SIS leads to final features in which changes in volume are minimal and can be controlled by varying the number of SIS cycles or other SIS parameters such as adsorption/purge time or temperature . With regard to the effect of infiltration on pattern quality, there is evidence of improved line edge roughness (LER), especially for low- and midfrequency roughness regimes, whereas surface roughness, another sensitive parameter, showed a modest increase after infiltration . Roughness analysis in ref was performed on the top surface of PMMA/SIS sub-100-nm lithographic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…We had earlier shown a high degree of control over the incorporation of the organometallic precursor by using atomic layer deposition, with the resulting oxide nanostructures enabling nanolithography down to sub-10 nm regime [35]. This was followed by several other investigations in literature focusing on vapor phase incorporation of metal-organic precursors within different block copolymer DOI: http://dx.doi.org/10.5772/intechopen.89064 domains using ALD processes [87][88][89][90][91]. It is important that the nanolithography process is optimized to not widen standard deviations between the features or across the wafer.…”
Section: Metal Nanopillars Arraysmentioning
confidence: 99%
“…Following the back-etch process, the individual samples were stained using selective growth of Al 2 O 3 in the PMMA domain using sequential infiltration synthesis (SIS) process [14,15]. SIS process, which enables growth of metal oxides inside polymer and BCP films with high selectivity to BCP polar domains [16], can be used to enhance the etch contrast between the BCP domains and improve pattern transfer [17,18]. It was recently shown that SIS is also an excellent staining process for BCPs since it results in high imaging contrast and it is highly stable under the electron beam [14,15,19].…”
Section: Methodsmentioning
confidence: 99%